Streptococcus pneumoniae interactions with the complement system - Gil, Eliza; Noursadeghi, Mahdad; Brown, Jeremy S. (Frontiers in Cellular and Infection Microbiology, 2022)
Host innate and adaptive immunity to infection with Streptococcus pneumoniae is critically dependent on the complement system, demonstrated by the high incidence of invasive S. pneumoniae infection in people with inherited deficiency of complement components. The complement system is activated by S. pneumoniae through multiple mechanisms. The classical complement pathway is activated by recognition of S. pneumoniae by C-reactive protein, serum amyloid P, C1q, SIGN-R1, or natural or acquired antibody. Some S. pneumoniae strains are also recognised by ficolins to activate the mannose binding lectin (MBL) activation pathway. Complement activation is then amplified by the alternative complement pathway, which can also be activated by S. pneumoniae directly. Complement activation results in covalent linkage of the opsonic complement factors C3b and iC3b to the S. pneumoniae surface which promote phagocytic clearance, along with complement-mediated immune adherence to erythrocytes, thereby protecting against septicaemia. The role of complement for mucosal immunity to S. pneumoniae is less clear. Given the major role of complement in controlling infection with S. pneumoniae, it is perhaps unsurprising that S. pneumoniae has evolved multiple mechanisms of complement evasion, including the capsule, multiple surface proteins, and the toxin pneumolysin. There is considerable variation between S. pneumoniae capsular serotypes and genotypes with regards to sensitivity to complement which correlates with ability to cause invasive infections. However, at present we only have a limited understanding of the main mechanisms causing variations in complement sensitivity between S. pneumoniae strains and to non-pathogenic streptococci.